METHODOLOGY FOR ORGANIZING INDEPENDENT LEARNING ACTIVITIES IN THE ACADEMIC LYCEUMS OF THE MINISTRY OF INTERNAL AFFAIRS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article addresses the issues of effectively organizing independent learning activitiesof students in the academic lyceums under the Ministry of Internal Affairs. In particular, it presentsproposals and recommendations for organizing independent learning activities through a web-basedplatform.